A charge jornalística: estratégias de imagem em enunciações de humor icônico - Maggioni, Fabiano (2011)
This study focuses on analyzing the meanings and effects of sense produced by the cartoon's journalistic morphological elements, dynamic and scalar image. Therefore, it is the insertion of short redemption charge among journalists and the strategies that make use to communicate. Then, to theorize the plastic properties and semantics of the charge, as stated, trying to show the importance and significance of the ability of plastics and semantic elements, and these divided into interdiscourse polyphony. The theoretical and methodological approach adopted for the analysis of the cartoons based on the Theory of Image and Speech Analysis and is concerned with identifying the plastic elements, taken in their morphological, dynamic and scalar, its use and effects of sense produced and, jointly, their semantic content on the aspects of interdiscursivity and polyphony. As the iconic cartoon a text of considerable degree of abstraction, with this analysis is expected to identify collaborative action of the primary content of the plastic charge for composition of semantic content to which its author, speaker, is proposed.